(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
The article discusses the principles of choosing lexical and grammatical units for learning profession-oriented English. Principles of selection of linguistic materials in foreign practice are considered. Practices focus on the selection of grammatical units based on content-based language education. Grammatical structures and language functions are also emphasized. Vocabulary and grammar selection for "Veterinary Science" was made on this basis of categories of language material for educational purposes. Selected lexical and grammatical units represent the field "Veterinary Science" on semantic importance, frequency of use and language functions of units.